Comparison of Tool Wear Rate of Insert Lathe TNMG160404-MA and TNMG160404-TF - Suwanda, Totok; Aji Wijayanto, Nur; Ardiyansyah, Nur (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Lathe machines are used to work on cylindrical objects. Tool wear is often a problem in the turning process and impacts the results of the machining process. The research aims to compare lathe insert tool wear levels TNMG160404-MA and TNMG160404-TF. The research used the experimental method directly using a lathe with variable machining on feeding (f) 0.04 mm/rev and 0.08 mm/rev, spindle (n) 540 rpm, and depth of cut (a) 4 mm. Tool wear was measured using an optical microscope by measuring the maximum edge wear on the tool (VBmax) and to determine the significance of tool wear using statistical analysis. The results showed wear level insert tool of TNMG160404-MA at a feeding of 0.04 mm/put an average of VBmax = 85.00(μm) and a feeding of 0.08 mm/put VBmax = 63.23(μm). TNMG160404-TF insert tool wear at 0.04 mm/put feed VBmax = 76.18(μm) and 0.08 mm/put feed VBmax = 58.43(μm). On a feeding, 0.08 mm/put motion, the standard deviation (s) of the TNMG160404-MA insert tool is 16.2, and the standard deviation (s) of the TNMG160404-TF insert tool is 17.8. On a feeding of 0.08 mm/rev, the results of t-count = 0.630 and t-table = 2.101, so t-count < t-table (0.630 < 2.101), the statistical analysis results using the t-test showed no significant difference in the level of wear of the two types insert tools.